Global Workspace Dynamics: Cortical “Binding and Propagation” Enables Conscious Contents - Baars, Bernard J.; Franklin, Stan; Ramsøy, Thomas Z. (Frontiers in Psychology, 2013)
A global workspace is a hub of binding and propagation in a population of loosely coupled signaling elements. Global workspace (GW) architectures recruit many distributed, specialized agents to help resolve focal ambiguities. In the brain, conscious experiences may reflect a global workspace function. For animals the natural world is full of fitness-related ambiguities, suggesting a general adaptive pressure for brains to resolve focal ambiguities quickly and accurately. In humans and related species the cortico-thalamic (C-T) core is believed to underlie conscious aspects of perception, thinking, learning, feelings of knowing, emotions, imagery, working memory and executive control. The C-T core has many anatomical hubs, but conscious percepts are unitary and internally consistent at any given moment. The repertoire of conscious contents is a large, open set. These points suggest that a brain-based GW capacity cannot be localized in a single anatomical hub. Rather, it should be sought in a dynamic capacity for adaptive binding and propagation of neural signals over multi-hub networks. We refer to this as dynamic global workspace theory (dGW). In this view, conscious contents can arise in any region of the C-T core when multiple signal streams settle on a winner-take-all equilibrium. The resulting bound gestalt may ignite an any-to-many broadcast, lasting ~100-200 ms, and trigger widespread adaptation in established networks. Binding and broadcasting may involve theta/gamma or alpha/gamma phase coupling. Conscious contents (qualia) may reflect their sources in cortex. Sensory percepts may bind and broadcast from posterior regions, while non-sensory feelings of knowing (FOKs) may be frontotemporal. The small focal capacity of conscious contents may be the biological price to pay for global access. We propose that in the intact brain the hippocampal/rhinal complex may support conscious event organization as well as episodic memory coding.